Pilot Study on Therapeutic System Design for Pressure Ulcer Management: Feasibility and Initial Findings - Lovindo Nulova; Husneni Mukhtar; Wahmisari Priharti; Maudina Citra Febriani; Ghibran Herlangga Zahra Rievansa; Fenty Alia (Jurnal Serambi Engineering, 2024)
Pressure ulcers or Decubitus Ulcers are injuries to the skin and underlying tissue due to prolonged pressure and friction that cause heat that damages skin tissue, generally occurring in bedridden patients who have difficulty moving and changing their position. Pressure ulcer treatment relies on conventional methods, with prevention as the primary step. Wound care is often overcome by cleaning the wound and changing the bandage regularly, although this method requires a long time and patience until the wound can gradually improve. Prevention is done by helping to change the patient's sleeping position regularly every few hours. This study aims to create a device that can help accelerate the healing process of pressure ulcers by using light therapy exposed to skin with pressure ulcers. A few variations of experiments were carried out on several mice that were conditioned to have pressure ulcers. Hence, the wound's healing time rate in each mouse with no treatment, treatment with 50% light intensity, and 100% light intensity, respectively, are 7%, 34%, and 82%. This pilot study showed improvement in pressure ulcers on the surface of the mouse skin within seven days, where wound healing was 2 to 3 days faster than without treatment. In conclusion, this study has demonstrated the feasibility of providing a therapeutic healing effect on the skin of mice and can be further developed in the future.